Integrated optical-thermal-electrical modeling of compound parabolic concentrator based photovoltaic-thermal system. (1st January 2022) - Parthiban, Anandhi; Mallick, T.K.; Reddy, K.S.
Highlights: A coupled multi-physics model is proposed for the CPC-PV/T system. A multi-physical model is used to analyze the glazed and unglazed CPV/T systems. Non-uniform flux obtained from ray tracing is mapped on to the solar cell in the FVM. A correlation for the average total Nusselt number in a glazed CPC is proposed. PV temperature profile was accurately obtained by the coupled multi-physics model. Abstract: The main aim of this work is to propose an integrated optical, thermal and electrical model to obtain the overall performance of a concentrated photovoltaic-thermal system (CPV/T). Monte Carlo ray-tracing (MCRT) simulations are done to obtain the flux profile on the absorber of a compound parabolic concentrator (CPC) for various angles of incidence. The obtained heat flux is mapped onto the solar cell in the finite volume method (FVM) to obtain its temperature profile. The modelling is done for both glazed and unglazed compound parabolic concentrator-photovoltaic/thermal (CPC-PV/T) systems using uniform (average heat flux) and non-uniform heat flux distribution. The obtained numerical results are compared with experimental results available in the literature. The results show that the prediction is accurate, with a maximum deviation in solar cell temperature of less than 3%. The deviations obtained when using non-uniform heat flux are much less than when using average heat flux. The temperature contours show that the temperature profile of the photovoltaic module obtained by using local non-uniform heat flux is different from the temperature profile obtained by using average heat flux, and these results will have a greater impact when designing a cooling system. The absorbed radiation from the optical analysis and average cell temperature from the thermal analysis are given to the five parameter electrical model of a solar photovoltaic cell to obtain the electrical power output. With the results of the integrated optical-thermal and electrical model, the overall useful power from both glazed and unglazed CPC-PV/T systems is calculated. The results show that the performance of the unglazed CPC-PV/T system is superior to the glazed CPC-PV/T system in terms of electrical and overall system output. This work demonstrates the need for a local heat flux profile and a coupled multi-physics model to accurately predict the performance of a concentrated photovoltaic/thermal (CPV/T) system.